Pembrolizumab plus chemotherapy-induced pneumonitis in chemo-naïve patients with non-squamous non-small cell lung cancer: A multicentre, retrospective cohort study. (June 2021) - Fujimoto, Daichi; Miura, Satoru; Yoshimura, Kenichi; Wakuda, Kazushige; Oya, Yuko; Yokoyama, Toshihide; Yokoi, Takashi; Asao, Tetsuhiko; Tamiya, Motohiro; Nakamura, Atsushi; Yoshioka, Hiroshige; Haratani, Koji; et al.
Abstract: Introduction: Despite the extensive use of the combination of cytotoxic chemotherapy and programmed cell death protein 1/programmed death-ligand 1 checkpoint inhibitors for cancer treatment, the incidence and characteristics of pneumonitis caused by this combination therapy have not been examined in clinical settings. Methods: We conducted a 36-centre, retrospective cohort study in patients with chemo-naïve advanced non-squamous non-small cell lung cancer who received a combination of platinum, pemetrexed and pembrolizumab between December 2018 and June 2019. Results: The study comprised 299 patients. The most frequent grade ≥3 non-hematologic adverse event was pneumonitis. There were 37 patients (12.4%, 95% CI 8.9–16.7) with all-grade pneumonitis and 10 (3.3%, 95% CI 1.6–6.1) with grade ≥3 pneumonitis. Of these, 21 (7.0%, 95% CI 4.4–10.5) and 9 patients (3.0%, 95% CI 1.4–5.6) developed all-grade and grade ≥3 pneumonitis within 90 days after initiating the combination therapy, respectively. The median time to treatment failure and progression-free survival was 5.9 (95% CI 5.0–6.8) and 7.5 (95% CI 6.5–8.7) months, respectively. In the survival analysis after adjusting for immortal time bias, pneumonitis was independently associated with shorter progression-free survival (HR 1.99, 95% CI 1.07–3.69, P  = 0.03) and overall survival (HR 3.03, 95% CI 1.12–8.20, P  = 0.03). Conclusions: Treatment-related pneumonitis occurred at a higher rate in the real-world population than that reported previously; it led to worse survival outcomes. Pneumonitis requires more attention. Additional studies are required to improve the safety of this combination therapy. Trial registration number: UMIN000038084 Highlights: Data on pembrolizumab plus chemotherapy-induced pneumonitis are limited. We conducted a 36-centre, retrospective cohort study. Treatment-related pneumonitis occurred at a higher rate in real-world settings. After adjusting for immortal time bias, pneumonitis led to worse survival outcomes. Our findings indicate that pneumonitis requires the careful attention of clinicians.